Seroprevalence of strongyloidiasis and toxocariasis among hypereosinophilic patients seeking care at diagnostic centers in Tehran, Iran - Zohre Fakhrieh- Kashan; Eshrat Beigom Kia; Mohammad Taghi Haghi Ashtiani; Seyed Reza Dabaghi; Mohammad Amin Sari; Enayat Darabi (Clinical Epidemiology and Global Health)
Background: Hypereosinophilia is characterized by an increase in eosinophil levels above the normal range. Secondary hypereosinophilia is frequently seen in helminth infections and allergic conditions. If not diagnosed and managed promptly, eosinophilia can result in various complications impacting health. The aim of this study was to explore the seroprevalence of Strongyloides stercoralis and Toxocara spp. among hypereosinophilic patients undergoing evaluation at selected diagnostic centers in Tehran. Methods: A comprehensive questionnaire was completed, and a blood sample was collected from each participant. The seropositivity of helminth infections was ascertained through indirect enzyme-linked immunosorbent assay (ELISA) employing commercially procured kits for discerning anti-S. stercoralis and anti-Toxocara spp. IgG antibodies. Statistical analysis was conducted using SPSS 21 software. Results: Of the 135 participants in this study, 61 (45.2 %) were male and 74 (54.8 %) were female. The seropositivity rates for strongyloidiasis and toxocariasis were found to be 9.6 % and 0.74 %, respectively. Among the various underlying medical conditions observed in the participants, Type 2 Diabetes (T2D) was the most prevalent, and it showed a significant association with seropositivity for strongyloidiasis (p < 0.05). Conclusion: The seropositivity for S. stercoralis was higher than that for Toxocara spp.. The significant association between seropositivity for S. stercoralis and diabetes underscores the importance of conducting community-based studies and implementing screening initiatives targeting high-risk populations to assess the seroprevalence of strongyloidiasis.